Novel mutations in TRPM6 gene associated with primary hypomagnesemia with secondary hypocalcemia. Case report - Papez, Jan; Starha, Jiri; Slaba, Katerina; Hubacek, Jaroslav A; Pecl, Jakub; Aulicka, Stefania; Urik, Milan; Ceylaner, Serdar; Vesela, Petra; Slaby, Ondrej; Jabandziev, Petr (Biomedical papers, 2021)
Background. Primary hypomagnesemia with secondary hypocalcemia (HSH) is a rare genetic disorder. Dysfunctional transient receptor potential melastatin 6 causes impaired intestinal absorption of magnesium, leading to low serum levels accompanied by hypocalcemia. Typical signs at initial manifestation are generalized seizures, tetany, and/or muscle spasms. Case report. We present a 5 w/o female manifesting tonic-clonic seizures. Laboratory tests detected severe hypomagnesemia and hypocalcemia. The molecular genetic analysis revealed two novel mutations within the TRPM6 gene c.3308dupC (p.Pro1104Thrfs*28) (p.P1104Tfs*28) and c.3958C>T (p.Gln1302*) (p.Q1302*) and the patient was successfully treated with Mg supplementation. Conclusion. Ion disbalance should be taken into account in the differential diagnosis of infantile seizures. Accurate diagnosis of HSH together with appropriate treatment are crucial to prevent irreversible neurological outcomes.
Keywords: hypomagnesemia; hypocalcemia; transient receptor potential melastatin 6; infantile seizures